Sensory transduction in vomeronasal neurons: evidence for G alpha o, G alpha i2, and adenylyl cyclase II as major components of a pheromone signaling cascade - Berghard, A (J Neurosci, 1996)
The mammalian vomeronasal organ (VNO) is an accessory olfactory structure implicated in the sensing of pheromones. Although virtually nothing is known about sensory transduction in the mammalian VNO, recent findings have raised the possibility that it proceeds via a G- protein-coupled mechanism and involves a cyclic nucleotide-gated ion channel as in the nasal olfactory epithelium. To investigate this possibility, we cloned G-protein alpha subunits, adenylyl cyclases, and guanylyl cyclases that are expressed in the VNO and examined their patterns of expression. Of seven G alpha subunits identified as being expressed in the VNO, we found that mRNAs encoding only two, G alpha o and G alpha i2, are highly expressed in VNO neurons. Moreover, G alpha o and G alpha i2 are highly expressed by separate subsets of neurons that are located in different regions of the VNO neuroepithelium. Immunohistochemical studies show that both G alpha o and G alpha i2 are enriched in VNO microvilli, suggesting that G-proteins containing both of these alpha subunits may be involved in VNO sensory transduction. Of the adenylyl and guanylyl cyclases that we cloned, we found that only one, adenylyl cyclase type II, is highly expressed in VNO neurons; furthermore, it is expressed by both G alpha o+ and G alpha i2+ subsets. Our findings suggest that spatially segregated subsets of VNO neurons may use different, but related, sensory transduction pathways in which G-proteins and an adenylyl cyclase play major roles.